2018
DOI: 10.1080/15548627.2018.1507439
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy controls neonatal myogenesis by regulating the GH-IGF1 system through a NFE2L2- and DDIT3-mediated mechanism

Abstract: Macroautophagy/autophagy is emerging as an important process in adult muscle stem cells functions: it regulates metabolic reprogramming during activation from a quiescent state, maintains stemness and prevents senescence. We now show that autophagy is specifically required for neonatal myogenesis and muscle development. Specific deletion of Atg7 in PAX7 (paired box 7) precursors led in mice to a dwarf phenotype, with an effect restricted to the neonatal phase of muscle development. Atg7 knockdown suppressed ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 64 publications
0
27
0
Order By: Relevance
“…Recently, it was shown that muscle specific deletion of Atg7, a key upstream marker for the autophagic regulation, led to a severe retardation of postnatal skeletal muscle development (Zecchini et al . ), suggesting an important role of autophagic system for neonatal muscle growth. Furthermore, ablation of either fusion (Papanicolaou et al .…”
Section: Discussionmentioning
confidence: 97%
“…Recently, it was shown that muscle specific deletion of Atg7, a key upstream marker for the autophagic regulation, led to a severe retardation of postnatal skeletal muscle development (Zecchini et al . ), suggesting an important role of autophagic system for neonatal muscle growth. Furthermore, ablation of either fusion (Papanicolaou et al .…”
Section: Discussionmentioning
confidence: 97%
“…The noncanonical KEAP1-NRF2 pathway has been suggested to have a role in development, disease and, specifically, cancer. For example, a deficiency of Atg7 in paired box 7 (Pax7)-positive muscle satellite cells (Atg7 F/F ;Pax7-Cre mice) results in dwarfism and decreased skeletal muscle mass in male mice only after P14, both of which are due to cell proliferation defects through decreased NRF2-target gene expression in the satellite cells (Zecchini et al, 2018). In this study, we found that an activated noncanonical KEAP1-NRF2 pathway resulted in a maturation defect of the GCTs in the SMGs of Insig1/2 cKO and Atg7 cKO mice through suppressed Foxa1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential mechanism whereby IGF-1 affects SC function is via regulation of autophagy. Zecchini et al showed that autophagy is required for neonatal myogenesis and muscle development [ 137 ]. Atg7 is an E1-like activating enzyme that regulates fusion of peroxisomal and vacuolar membranes during autophagy, and Atg7 knockdown in SCs caused severe reduction in neonatal myogenesis.…”
Section: Igf-1 Satellite Cells and Skeletal Muscle Regenerationmentioning
confidence: 99%